A mid-infrared dual-comb spectrometer in step-sweep mode for high-resolution molecular spectroscopy. (September 2022) - Lepère, Muriel; Browet, Olivier; Clément, Jean; Vispoel, Bastien; Allmendinger, Pitt; Hayden, Jakob; Eigenmann, Florian; Hugi, Andreas; Mangold, Markus
Highlights: Table-top dual-comb spectrometer in high-resolution step-sweep mode. Mid-infrared spectra with 10 −4 cm −1 wavenumber accuracy. Gapless coverage of 50 cm −1 . Application to N2 -collisional broadening of methane lines. Abstract: To meet the challenges of high-resolution molecular spectroscopy, increasingly sophisticated spectroscopic techniques were developed. For a long time FTIR and laser-based spectroscopies were used for these studies. The recent development of dual-comb spectroscopy at high-resolution makes this technique a powerful tool for gas phase studies. We report on the use and characterization of the IRis-F1, a tabletop mid-infrared dual-comb spectrometer, in the newly developed step-sweep mode. The resolution of the wavenumber axis is increased by step-wise tuning (interleaving) and accurate measurement of the laser center wavelength and repetition frequency. Doppler limited measurements of N2 O and CH4 reveal a wavenumber accuracy of 10 −4 cm −1 on the covered range of > 50 cm −1 . Measured half-widths of absorption lines show no systematic broadening, indicating a negligible instrument response function. Finally, measurements of nitrogen pressure broadening coefficients in the ν4 band of methane show that quantum cascade laser dual-comb spectroscopy in step-sweep mode is well adapted for measurements of precision spectroscopic data, in particular line shape parameters.